AGE DETERMINATION OF LIMESTONE ROCKS LEANG - LEANG CAVE COMPIL- ER THROUGH ACTIVITY MEASUREMENTS 14C USING LSC - Syarifuddin Syarifuddin; Muhammad Zakir; Alfian Noor (Hasanuddin University, 2014)
Age Determination of Limestone of Leang - Leang Cave Through Activity Measurements of 14C Using LSC. This research has been carried out by using limestone samples taken from Leang- Leang Cave, Maros. Limestone is one of the environmental samples with a constituent of calcite mineral (CaCO3) which is derived from the remains of flora and fauna that has been weathered and petrified. Sample preparation was done physically and chemically. Preparation of chemically by using a mixture of NaOH with 30% H2O2 followed by a mixture of HClO4 with 30% H2O2, and the last with HCl solution to produce a clean sample with a weight reduction of 3,36% - 4,44%. Car- bonate matrix samples as CO2 is produced by reaction with 85% H3PO4 and absorbed by 1M KOH solution as K2CO3. The total carbon in the sample solution is 0,6144 - 0,9696 grams obtained through titration method. Radiocarbon dating method based on the measurement of the specific activity of the samples obtained from the results of counts LSC (Liquid Scintilation Counter) Hidex 300 SL. The specific activity of both of samples were 1,609±0,0359 DPM/g C and 7,718±0,109 DPM/g C. Age of both of limestone samples which were calculated from the specific activity were 25.607,403 ± 919,305 years and 8457,792 ± 921,899 years for BG I and BG II, re- spectively.